On the Method of Evolutionary Psychology and Its Applicability to Consumer Research. (June 2017) - Saad, Gad
There is a growing interest among marketing scholars to examine the evolutionary bases of a wide range of consumer phenomena. While specific evolutionary hypotheses are typically tested using tools familiar to marketing researchers (e.g., experiments, surveys), the method of evolutionary psychology is rooted in its unique epistemology (the manner in which knowledge is generated and organized), which comprises three elements: (1) the distinction between proximate and ultimate explanations, (2) the building of nomolological networks of cumulative evidence (triangulation of convergent lines of evidence), and (3) an organizing tree of knowledge. The purpose of this article is to describe this process using marketing-relevant examples as a means of providing a framework of best practices to marketing scholars aiming to incorporate the evolutionary lens within their research programs.